Solve for h h(-3)=2/3*(-3)+1

Math
h(-3)=23⋅(-3)+1
Simplify.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Factor 3 out of -3.
h(-3)=23⋅(3(-1))+1
Cancel the common factor.
h(-3)=23⋅(3⋅-1)+1
Rewrite the expression.
h(-3)=2⋅-1+1
h(-3)=2⋅-1+1
Multiply 2 by -1.
h(-3)=-2+1
Add -2 and 1.
h(-3)=-1
h(-3)=-1
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in h(-3)=-1 by -3.
h(-3)-3=-1-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
h⋅-3-3=-1-3
Divide h by 1.
h=-1-3
h=-1-3
Dividing two negative values results in a positive value.
h=13
h=13
The result can be shown in multiple forms.
Exact Form:
h=13
Decimal Form:
h=0.3‾
Solve for h h(-3)=2/3*(-3)+1

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top